2004
DOI: 10.1152/ajpendo.00035.2004
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-independent effects of GLP-1 on canine liver glucose metabolism: duration of infusion and involvement of hepatoportal region

Abstract: . Insulin-independent effects of GLP-1 on canine liver glucose metabolism: duration of infusion and involvement of hepatoportal region. Am J Physiol Endocrinol Metab 287: E75-E81, 2004. First published March 16, 2004 10.1152/ ajpendo.00035.2004.-Whether glucagon-like peptide-1 (GLP-1) has insulin-independent effects on glucose disposal in vivo was assessed in conscious dogs by use of tracer and arteriovenous difference techniques. After a basal period, each experiment consisted of three periods (P1, P2, P3) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 45 publications
(70 reference statements)
3
49
2
3
Order By: Relevance
“…The present study demonstrated that the beneficial effects of exendin-4 were also found in CaMTg diabetic mice, and that its major effect was to maintain the b-cell mass, because 1) the exendin-4 treatment increased the insulin contents of the pancreas and islets and 2) it also expanded the insulin-positive area in both nTg and CaMTg mice. Although the extrapancreatic effects of GLP-1 have been reported to participate in the hypoglycemic effects of exendin-4 (Egan et al 1994, Luque et al 2002, Dardevet et al 2004), we could not find any effect of the treatment on plasma glucose levels in the insulin tolerance test.…”
Section: Discussioncontrasting
confidence: 74%
“…The present study demonstrated that the beneficial effects of exendin-4 were also found in CaMTg diabetic mice, and that its major effect was to maintain the b-cell mass, because 1) the exendin-4 treatment increased the insulin contents of the pancreas and islets and 2) it also expanded the insulin-positive area in both nTg and CaMTg mice. Although the extrapancreatic effects of GLP-1 have been reported to participate in the hypoglycemic effects of exendin-4 (Egan et al 1994, Luque et al 2002, Dardevet et al 2004), we could not find any effect of the treatment on plasma glucose levels in the insulin tolerance test.…”
Section: Discussioncontrasting
confidence: 74%
“…This was further confirmed in dogs (34) but remains contradictory (35,36), depending on the model studied. Balkan et al (37) showed that portal GLP-1 increased insulin secretion through a mechanism that requires the autonomic nervous system to transmit the glucose signal to the pancreas.…”
Section: Glp-1r-dependent Actions Of Oligofructosementioning
confidence: 61%
“…It is possible that the high portal GLP-1 concentrations might also have insulinindependent effects on glucose metabolism via neural reflexes, e.g. HGP [84]. Further support for the importance of GLP-1 for the improvement in glycaemic control comes from experimental surgery in both animals and humans involving ileal interposition, where a segment of ileum is interposed within the upper jejunum, thereby increasing the exposure of the L cells to ingested nutrients without bypassing the duodenum.…”
Section: Discussionmentioning
confidence: 99%